A critical forest art practice: the Black Wood of Rannoch. (17th February 2018) - Collins, Timothy Martin; Goto, Reiko; Edwards, David
Abstract: The Black Wood of Rannoch is the most significant Caledonian forest in the Southern Highlands. Working from within the tradition of environmental art research, the authors sought to make a contribution to ideas about cultural ecology and the value of forests such as the Black Wood. The goal of this article is to provide an overview of the steps taken to both experience the visual/sensual conditions and understand the social/cultural aspects of a forest classified as ancient semi-natural woodland. What has emerged is an understanding of the ways in which historic land conflicts reshaped it into its current ecologically robust yet semi-natural condition. However, the cultural content and public interest one would expect to find in relationship to a historically important remnant forest are largely missing. The recovery of that content and interest was the focus of this research.